How Political Party Handle Their Internal Problem? Comparative Studies Between The Nationalist Party and Islamic Party in Indonesia (Golkar and PKS) - Juswil, Addin Khaerunnisa; Purnomo, Eko Priyo; Nur Kasiwi, Aulia (Jurnal Review Politik, 2020)
In recent era, we can see so many party trapped into an internal conflict, one of them is Golkar and PKS, see two parties with different ideological foundations, which of course has a mechanism of different conflict resolution processes, but falls within the same internal conflict circle that is still related to the existence of party elites especially when the conflict is up to the binding decision of the Supreme Court then the author seeks to dig the political party in Indonesia in resolving the internal problems of the party so as not to affect the internal party. This paper use a qualitative methods with most of the data came from literature review and from secondary data from the party itself. The result of this paper is that party internal conflict aren’t causes by ideological things, but causes by elites needs. This can be solved by strengthen the position of party court and increasing the amount of member in party court.